Bacterial Analysis of Different Types of Milk (Pasteurized, Unpasteurized and Raw Milk) Consumed in Kathmandu Valley (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The presence of pathogenic bacteria in milk is the major public health concern resulting in food borne illness. The aim of this study is to determine the microbial quality of three different types of milk consumed in Kathmandu Valley with respect to the acceptable standard guideline and measure the antibiotic susceptibility pattern of the Escherichia coli and Staphylococcus aureus isolates.Methods: A total of 66 samples (16 pasteurized, 25 unpasteurized and 25 raw milk) were collected from various sites of Kathmandu Valley. Those samples were subjected for total plate count and total coliform count by pour plate method. Furthermore, identification was made for the presence of E. coli and S. aureus with biochemical tests.Results: The mean total plate count (TPC) of pasteurized, unpasteurized and raw milk was 1.2X106 cfu/ml, 2.3 X 107 cfu/ml and 2.0 X 107 cfu/ml respectively. And, the mean total coliform count (TCC) of pasteurized, unpasteurized and raw milk was 2.9 X 104cfu/ml, 6.3 X 105 cfu/ml and 1.6 X 105 cfu/ ml respectively. Coliforms were detected in 50%, 84% and 56% of the pasteurized, unpasteurized and raw milk sample respectively. E. coli and S. aureus were isolated from 18.8% and 12.5% of pasteurized, 40% and 16% of unpasteurized and 20% and 24% of the raw milk samples respectively. Among total E. coli isolates (n=18), 16.7% were susceptible to ampicillin whereas 100% isolates were susceptible to other tested antibiotics. Similarly, 33.3% and 66.7% of the isolated S. aureus were susceptible to penicillin and cefoxitin respectively, whereas all S. aureus isolates were sensitive to all other antibiotics.Conclusion: The mean value of TPC and TCC of pasteurized and raw milk exceed the standard guideline by FDA. Higher total plate count and presence of coliforms (also E. coli) and S. aureus in this study necessitates the close monitoring of the pasteurization process and post pasteurization process (packaging, transportation, storage etc.).